Autorefraction, Retinoscopy, Javal’s Rule, and Grosvenor’s Modified Javal’s Rule: The Best Predictor of Refractive Astigmatism - Kofi Asiedu; Samuel Kyei; Emmanuel Ekow Ampiah (Journal of Ophthalmology)
The aim of the study was to determine the level of agreement between Javal’s rule, autorefraction, retinoscopy, and refractive astigmatism and to determine which technique is the most suitable substitute when subjective refraction is not applicable using a clinical sample. A total of 36 subjects, 14 males and 22 females, were involved in this study. The intraclass correlation coefficients between subjective refraction, autorefraction, and retinoscopy were 0.895 and 0.989, respectively, for the spherical equivalent. The Bland-Altman 95% limits of agreement between subjective refraction and autorefraction; subjective refraction and retinoscopy; and autorefraction and retinoscopy were −2.84 to 3.58, −0.88 to 1.12, and −3.01 to 3.53, respectively, for the spherical equivalent. The intraclass correlation coefficients between spectacle total astigmatism and the following techniques were as follows: retinoscopy (0.85); autorefraction (0.92); Javal’s rule (0.82); and Grosvenor et al. version (0.85). The Bland-Altman 95% limits of agreement between subjective refraction and autorefraction; subjective refraction and retinoscopy; subjective refraction and Javal’s rule; and subjective refraction and Grosvenor et al. version were −0.87 to 1.25, −1.49 to 1.99, −0.73 to 1.93, and −0.89 to 1.7, respectively, for the total astigmatism. The study showed that autorefraction and Javal’s rule may provide a starting point for subjective refraction cylinder power determination but only retinoscopy may satisfactorily replace subjective refraction total astigmatism when subjective refraction is not applicable.